Helping tomorrow’s doctors to become reflective practitioners through digital storytelling - Sumner, Tony (2020)
Background: Latest medical education guidelines in the UK stress the need for doctors to be capable reflective practitioners. However, traditional cultures and methods within medical education departments develop and deliver reflective programmes that are mechanistic and ineffective. This paper describes two programmes run for medical students at two different UK universities based on Reflective digital storytelling principles, and their outcomes. Methods: The Patient Voices Reflective Digital Storytelling process was used to provide reflective opportunities for medical students at the University of Leicester (N=5) in 2008 and Kings College London (N=4) in 2014. In both cases the normal process was adapted to suit student timetables, examination schedules, etc. Experience running Patient Voices Reflective Digital Storytelling workshops for newly-qualified nurses, etc. was used to inform facilitative approaches. Different adaptations were needed in each institution. Results: In both cases all students created reflective stories. Several (N=6) found the process so engaging they created two stories. Student feedback in both cases was powerfully positive, with students arguing at the launch of the stories created for universal adoption of this approach to reflection within their institutions. Students reported bonding as a group and feeling greater empathy with patients while on placement. Conclusions: Digital storytelling can provide the basis for a methodology within which medical students can deeply and effectively reflect on experiences of personal life, training and early practice, but key to this is ensuring a safe facilitative environment within which they can truly reflect rather than merely fill in reflection forms.